Impact of Pretransplant Donor BK Viruria in Kidney Transplant Recipients. (14th March 2019) - Tan, Susanna K; Huang, Chunhong; Sahoo, Malaya K; Weber, Jenna; Kurzer, Jason; Stedman, Margaret R; Concepcion, Waldo; Gallo, Amy E; Alonso, Diane; Srinivas, Titte; Storch, Gregory A; Subramanian, Aruna K; et al.
Abstract: Background: BK virus (BKV) is a significant cause of nephropathy in kidney transplantation. The goal of this study was to characterize the course and source of BKV in kidney transplant recipients. Methods: We prospectively collected pretransplant plasma and urine samples from living and deceased kidney donors and performed BKV polymerase chain reaction (PCR) and immunoglobulin G (IgG) testing on pretransplant and serially collected posttransplant samples in kidney transplant recipients. Results: Among deceased donors, 8.1% (17/208) had detectable BKV DNA in urine prior to organ procurement. BK viruria was observed in 15.4% (6/39) of living donors and 8.5% (4/47) of deceased donors of recipients at our institution ( P = .50). BKV VP1 sequencing revealed identical virus between donor–recipient pairs to suggest donor transmission of virus. Recipients of BK viruric donors were more likely to develop BK viruria (66.6% vs 7.8%; P < .001) and viremia (66.6% vs 8.9%; P < .001) with a shorter time to onset (log-rank test, P < .001). Though donor BKV IgG titers were higher in recipients who developed BK viremia, pretransplant donor, recipient, and combined donor/recipient serology status was not associated with BK viremia ( P = .31, P = .75, and P = .51, respectively). Conclusions: Donor BK viruria is associated with early BK viruria and viremia in kidney transplant recipients. BKV PCR testing of donor urine may be useful in identifying recipients at risk for BKV complications. Abstract : Donor BK viruria is associated with early BK viruria and viremia in kidney transplant recipients. BK virus polymerase chain reaction testing of donor urine may be useful in identifying recipients at risk for BK virus complications.